C-terminal HSP90 inhibitor L80 elicits anti-metastatic effects in triple-negative breast cancer via STAT3 inhibition. (10th April 2019) - Cho, Tae-Min; Kim, Ji Young; Kim, Yoon-Jae; Sung, Daeil; Oh, Eunhye; Jang, Seojin; Farrand, Lee; Hoang, Van-Hai; Nguyen, Cong-Truong; Ann, Jihyae; Lee, Jeewoo; Seo, Jae Hong
Abstract: Triple-negative breast cancer (TNBC) is an aggressive heterogeneous disease with a divergent profile. It has an earlier tendency to form metastases and is associated with poor clinical outcomes due to the limited treatment options available. Heat-shock protein (HSP90) represents a potential treatment target as it promotes tumor progression and metastasis by modulating the maturation and stabilization of signal transduction proteins. We sought to investigate the efficacy of the C-terminal HSP90 inhibitor L80 on cell proliferation, breast cancer stem cell (BCSC)-like properties, tumor growth and metastasis. L80 suppressed cell viability and concomitantly inhibited AKT/MEK/ERK/JAK2/STAT3 signaling in TNBC cells but did not induce cytotoxicity in normal cells. L80 effectively targeted BCSC-like traits, together with significant reductions in the CD44high/CD24low-population, ALDH1 activity and mammosphere forming-ability. In support of the in vitro observations, L80 administration caused significant impairment in tumor growth, angiogenesis and distant metastases in an orthotopic allograft model with BCSC-enriched cells in vivo . These phenomena were associated with the suppression of BCSC-like characteristics and STAT3 dysfunction. Our findings highlight properties of the L80 compound that may be useful in suppressing metastatic TNBC. Highlights: The C-terminal HSP90 inhibitor L80 targets cancer stem-like properties. L80 inhibits HSP90 client protein kinases including AKT, MEK, JAK and STAT3. L80 suppresses tumor growth and distant TNBC metastases in vivo. Antitumor activity of L80 is associated with dysregulation of STAT3 activation.